Biochemistry - Zubay, Geoffrey L. (Wm.C. Brown Publishers, 1993)
This biochemistry book has chapters devoted solely to vitamins, co-enzymes and metal co-factors, and the complete description of protein purification. Chapters new to this edition include an analysis of the functional diversity of proteins, immunobiology and carcinogenesis, and oncogenes.